Change-event steals "athlete" from "college athlete": perceived impact and depression, anxiety, and stress - Garver, M. J.; Gordon, A. M.; Philipp, N. M.; Huml, M. R.; Wakeman, A. J. (Journal of Multidisciplinary Healthcare, 2021)
Introduction: This research sought to establish the impact of the change-event of COVID-19 on college athletes and members of other campus groups (eg, marching band, eSports, Reserve Officers Training Corps). The specific purpose was to assess the perceived impact and impact on mental health (eg, depression, anxiety, and stress). Methods: The survey battery presented a total of 37 items. Demographic, sport or group-specific, and academic-related questions were included alongside the assessment of psychological well-being coming from the Depression Anxiety Stress Scale-21. Results: There were 249 participants completing some or all of the survey battery. It is notable that 172 participants (69.1%) indicated "a lot has changed". Common one-word responses to the experience surrounding this change-event were feeling disappointment, upset, frustrated, sadness, annoyance, and depression. Life events that conjured similar magnitude of emotion included significant injury, surgery, and losing a loved one. There were no differences by sport for the depression subscale, but 110 participants reported elevated scores and females had a higher mean depression subscale score compared with males. Differences between sports for the anxiety subscale were negated when evaluating Bonferroni correction for multiple tests, but 69 participants reported elevated scores and females had a higher mean anxiety subscale score compared with males. There was no difference by sport for the stress subscale, but 77 participants reported elevated scores and females had a higher mean stress subscale score compared with males. Discussion: Authors urge the campus and athletics community to be diligent in monitoring the holistic wellness of college athletes and members of other campus groups. Mainly, we contend it is important to consider that COVID-19 is a significant and widespread change-event, and other change-events are known to have significant impact. We should consider that COVID-19 may be acutely and longitudinally impactful to the American college student.